Arterial relaxation is coupled to inhibition of mitochondrial fission in arterial smooth muscle cells: comparison of vasorelaxant effects of verapamil and phentolamine - Jing Jin; Xin Shen; Yu Tai; Shanliang Li; Mingyu Liu; Changlin Zhen; Xiuchen Xuan; Xiyue Zhang; Nan Hu; Xinzi Zhang; Deli Dong (Elsevier, 2017)
Mitochondria are morphologically dynamic organelles which undergo fission and fusion processes. Our previous study found that arterial constriction was always accompanied by increased mitochondrial fission in smooth muscle cells, whereas inhibition of mitochondrial fission in smooth muscle cells was associated with arterial relaxation. Here, we used the typical vasorelaxants, verapamil and phentolamine, to further confirm the coupling between arterial constriction and mitochondrial fission in rat aorta. Results showed that phentolamine but not verapamil induced vasorelaxation in phenylephrine (PE)-induced rat thoracic aorta constriction. Verapamil, but not phentolamine, induced vasorelaxation in high K+ (KPSS)-induced rat thoracic aorta constriction. Pre-treatment with phentolamine prevented PE- but not KPSS-induced aorta constriction and pre-treatment with verapamil prevented both PE- and KPSS-induced aorta constriction. Transmission electron microscopy (TEM) results showed that verapamil but not phentolamine inhibited KPSS-induced excessive mitochondrial fission in aortic smooth muscle cells, and verapamil prevented both PE- and KPSS-induced excessive mitochondrial fission in aortic smooth muscle cells. Verapamil inhibited KPSS-induced excessive mitochondrial fission in cultured vascular smooth muscle cells (A10). These results further demonstrate that arterial relaxation is coupled to inhibition of mitochondrial fission in arterial smooth muscle cells.